2018
DOI: 10.1111/febs.14591
|View full text |Cite
|
Sign up to set email alerts
|

A Cu2+ complex induces the aggregation of human papillomavirus oncoprotein E6 and stabilizes p53

Abstract: Papillomavirus oncoprotein E6 is a critical factor in the modulation of cervical cancer in humans. At the molecular level, formation of the E6-E6AP-p53 ternary complex, which directs p53's degradation, is the key instigator of cancer transforming properties. Herein, a Cu anthracenyl-terpyridine complex is described which specifically induces the aggregation of E6 in vitro and in cultured cells. For a hijacking mechanism, both E6 and E6AP are required for p53 ubiquitination and degradation. The Cu complex inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Notably, the coordination of Zn 2+ by the HPV16 E7 protein produces a compact environment leading to its self-assembly into spherical oligomers similar to those found in amyloids, whereas Zn 2+ depletion results in loss of its aggregation [ 219 , 220 , 221 ]. HPV E6 protein also forms Zn 2+ -dependent soluble agglomerates, whereas the metal chelating agent EDTA stabilizes its monomeric form and destabilizes existing agglomerates [ 89 ], and where Cu 2+ complexes also cause E6 aggregation, inhibiting its function [ 222 ]. Recent work has demonstrated that the keratinocyte-derived body’s epidermal barrier is formed by the filaggrin protein [ 223 ], a protein that phase-separates and that has been found to bind Cu 2+ and be regulated by Zn 2+ [ 224 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the coordination of Zn 2+ by the HPV16 E7 protein produces a compact environment leading to its self-assembly into spherical oligomers similar to those found in amyloids, whereas Zn 2+ depletion results in loss of its aggregation [ 219 , 220 , 221 ]. HPV E6 protein also forms Zn 2+ -dependent soluble agglomerates, whereas the metal chelating agent EDTA stabilizes its monomeric form and destabilizes existing agglomerates [ 89 ], and where Cu 2+ complexes also cause E6 aggregation, inhibiting its function [ 222 ]. Recent work has demonstrated that the keratinocyte-derived body’s epidermal barrier is formed by the filaggrin protein [ 223 ], a protein that phase-separates and that has been found to bind Cu 2+ and be regulated by Zn 2+ [ 224 ].…”
Section: Resultsmentioning
confidence: 99%
“…Molecularly, E6-E6AP-p53 complex leads to the destruction of p53, a vital mediator of pro-cancer transforming protein. The binding sites of E6AP and p53 facilitates the interaction of anthracenyl-terpyridine Cu 2+ complex with E6 [ 196 ]. The complex stimulated in vitro E6 aggregation in cultured cells.…”
Section: Trace Elements and Cervical Cancermentioning
confidence: 99%